The effect of the supported structured learning strategy on learning some soccer skills for middle school students A search received previously (Journal of the College of Basic Education, 2022)
The effect of the supported structured learning strategy on learning some soccer skills for middle school students Learning is not a process of acquiring information, but rather an inspired process in which the learner builds information and skill, which contributes to his increase. The student in self-learning may be more active because he analyzes the tasks presented to him by the teacher and always plans for the appropriate goals for his learning and to achieve those goals planned by Elm. Design and application of educational units according to the strategy of self-organized education and to identify the effect of the strategy of self-organized learning supported in learning some basic skills in football. The researchers used the experimental method for its suitability with the nature of the problem and the objectives of the research. The research community and its sample. The researchers deliberately identified the research community, the research from the students of the Iraq Middle School for Al-Bayan in the Directorate of Education of Baghdad Karkh third for the academic year 2021-2022, numbering 142 students. As for the research sample, it was chosen by the random method, as it was formed Of the fifth year preparatory students with four divisions, Division A 35 students, Division B 35 students, Division C 34 students, and Division D 38 students. The systematic random method was used to determine the two research groups, as Division (A) was chosen to be an experimental group and Division (D) a control group and lists each A research group is 10 students, so the research sample consists of (20) students, who make up 35.21% of the research community. As this percentage is representative and real for the research community, the exploratory experiment was applied by selecting (10) students from (C) to represent the sample of the exploratory experiment for skill tests and (10) from Division C. After that, the researchers determined the appropriate skills and tests as well as conducting a pilot experiment and conducting the test Al-Qibli and proceeded to apply 12 educational units according to the self-organized learning model, and after that he conducted the post-test and the researchers used the statistical bag to reach statistical results from which the most important conclusions crystallized, including the positive impact of the supported organized learning strategy in learning some football skills for the fifth grade preparatory students. Self-organized learning encourages students to contribute to creativity and innovation in proportion to their experiences, skills and personal talents. The self-organized learning strategy worked on gaining learners cognitive experience and has improved their self-organization process, memorization and retrieval process, and the learner became a participant in decision-making. The self-organized learning strategy contributed to providing Students' feedback worked to reduce common errors in skill performance.